Influences of Contingency Planning in Improving Preparedness of Tough Disaster Village Cadres in Facing Volcano Eruption Disaster in Blitar, East Java, Indonesia - Agus Khoirul Anam; Sri Winarni; Andi Hayyun Abiddin (Humanistic Network for Science and Technology (HNST), 2021)
The Village cadres' respite of death or of a calamity is the community as leading perpetrator of in the process of bringing into reality the spiritual or postponed for a while as well as technical and village. The purpose of this research to identify the influence of contingency planning in improving disaster preparedness or postponed for a while of having young village people in charge of disaster management deal with disaster of volcanic eruption. The quasi-experimental design was used. We recruited 25 the tough disaster village cadres with a total population sampling method. The analysis of the t-test showed the t-value of -5.269 and p-value of 0.001, it means that there was significant difference of the preparedness of tough disaster village cadres in facing volcanic eruptions disaster between before and after being given contingency planning. Keywords: contingency planning; preparedness; village; caders; volcano; disaster